Students’ perception and preference of feedback methods: enhancing the quality assurance of higher education institution - Al-Amri, Amal Said; Jani, Rohana; Zubairi, Yong Zulina; Kumar, Senthil (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study evaluated students’ perceptions about providing feedback and identified their preferred feedback methods. The study design comprised quantitative and qualitative approaches to ensure a better understanding of students’ perceptions and increase the study’s validity. A structured questionnaire was distributed in five higher education institutions (HEIs) in Oman, followed by a focus group discussion (FGD). A total of 614 students responded to the questionnaire. The quantitative data were analyzed using descriptive statistics, and the qualitative data were analyzed using thematic text analysis. It was observed that although students understand the importance of feedback, they feel that the methods can be improved. Furthermore, HEIs did not share the outcomes with the students, and therefore, students believed that HEIs were not considering their comments. Whilst students preferred anonymous online surveys, they believed that inperson meetings would be even more useful. This paper looked at how the educational well-being of students in Oman can be improved through the development of methods of seeking feedback from institutions. Additionally, this result can be applied worldwide to improve feedback mechanisms.